A method for nanoimprint fabrication of glass-based resin v-groove structure

CN122962885APending Publication Date: 2026-10-23华天慧创科技(西安)有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611146563.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本申请的主要目的在于提供一种玻璃基树脂V槽结构的纳米压印制备方法,旨在解决如何在避免对最终玻璃基板本体直接切削V槽的同时,提高玻璃基板表面树脂V槽结构在压印成型、固化和脱模后的复制完整性及批次一致性的技术问题

Benefits of technology

本申请通过母模翻制具有V形凸棱阵列的弹性工作模板,并使V形凸棱阵列在平面加载力作用下压入玻璃基板表面的压印胶层,从而在树脂结构层中复制形成V槽阵列,使最终玻璃基板本体无需进行V槽切削,有利于降低玻璃切削损伤风险;通过保持加压贴合并进行一次性整体紫外固化,有利于保持V槽轮廓;通过由模板一侧开始的渐进式脱模降低瞬时分离载荷;通过脱模后的恒温热处理,有利于提高树脂V槽结构的硬度或尺寸稳定性,从而提高复制完整性及批次一致性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962885A_ABST
    Figure CN122962885A_ABST
Patent Text Reader

Abstract

The application discloses a nano-imprint preparation method of a glass-based resin V-groove structure, which comprises the following steps: forming a female V-groove array on a female mold base material, and duplicating a polydimethylsiloxane elastic working mold with a V-shaped ridge array; performing alkaline ultrasonic cleaning on a glass substrate, and coating the glass substrate with a low-stress ultraviolet curing nano-imprint glue; applying a planar loading force by using a planar nano-imprint device, so that the V-shaped ridge array is pressed into the nano-imprint glue layer, and the molding surface of the mold is fully attached to the nano-imprint glue layer; performing one-time overall ultraviolet curing in a state of maintaining the pressure-attached state, then gradually demolding, and finally performing constant-temperature heat treatment on the obtained glass substrate and resin V-groove structure layer. The method avoids directly cutting the V-groove on the final glass substrate body, is favorable for reducing the risk of glass cutting damage, and improves the V-groove replication integrity and batch consistency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the fields of micro-nano optical structure manufacturing, nanoimprinting and optical glass processing technology, and in particular to a method for nanoimprinting a glass-based resin V-groove structure. Background Technology

[0002] V-groove arrays can be used for micro- and nano-optical structures, coupling structures, and precision alignment structures. Existing glass-based V-grooves are usually formed by cutting or milling glass substrates one piece at a time using diamond tools. However, glass is a brittle material, and direct cutting can easily cause chipping, micro-cracks, scratches, and residual stress at the groove opening, sidewalls, or bottom. Furthermore, piece-by-piece machining also has problems such as long processing time, tool wear, and difficulty in controlling batch dimensional consistency.

[0003] In the prior art, patent CN101339364B, a method for manufacturing microlens arrays using soft mold imprinting, discloses the use of a polydimethylsiloxane soft mold to transfer microstructures onto a UV-cured adhesive on the surface of a glass substrate, followed by UV curing while the mold and glass substrate are in contact. Patent US20040134786A1, "Mold for a V-groove fiber array baseblock and fabrication method thereof," discloses the idea of ​​preparing V-groove molds and using them for mass production. Based on the main disclosures of these documents, it is not apparent that they simultaneously and explicitly include the following complete process for glass-based resin V-groove structures: alkaline ultrasonic cleaning of the glass substrate followed by direct adhesive application, planar pressure molding, one-time overall UV curing under pressure, progressive demolding, and post-demolding isothermal heat treatment.

[0004] The technical problem that the existing technology cannot solve is: how to improve the replication integrity and batch consistency of the resin V-groove structure on the surface of the glass substrate after imprinting, curing and demolding while avoiding direct cutting of V-grooves on the final glass substrate body. Summary of the Invention

[0005] The main objective of this application is to provide a method for nanoimprinting a glass-based resin V-groove structure, aiming to solve the technical problem of how to improve the replication integrity and batch consistency of the resin V-groove structure on the glass substrate surface after imprinting, curing and demolding while avoiding direct cutting of the V-groove on the final glass substrate body.

[0006] To achieve the above objectives, this application provides a method for preparing a glass-based resin V-groove structure using nanoimprinting, comprising the following steps: S1. A mother V-groove array is formed on one side of the mother mold substrate, and a polydimethylsiloxane elastic working template is made based on the mother V-groove array. The forming surface of the elastic working template has a V-shaped convex ridge array that is complementary to the mother V-groove array. S2. The glass substrate is ultrasonically cleaned using an alkaline cleaning solution. After the cleaned glass substrate is dried, a nano-imprint adhesive is coated on one side of the glass substrate to form an imprint adhesive layer. S3. Orient the V-shaped convex ridge array toward the imprinting adhesive layer, and apply a planar loading force to the elastic working template and the glass substrate using a flat nanoimprinting device, so that the V-shaped convex ridge array is pressed into the imprinting adhesive layer, and the forming surface of the elastic working template is bonded to the imprinting adhesive layer. S4. While keeping the elastic working template and the glass substrate pressed together, the imprinting adhesive layer is subjected to overall ultraviolet irradiation to cure the nano-imprinting adhesive and form a resin structure layer. S5. After UV curing, the elastic working template is gradually peeled off from one side, so that the separation interface between the elastic working template and the resin structure layer is gradually advanced from one side to the opposite side, so that the V-groove array formed on the side of the resin structure layer away from the glass substrate is exposed. S6. The demolded glass substrate and the resin structural layer are subjected to constant temperature heat treatment to obtain a glass-based resin V-groove structure.

[0007] Optionally, in S1, the master mold substrate is glass or silicon, and the master V-groove array is formed by precision cutting, etching, or a combination of precision cutting and etching; the included angle of the V-groove array is 30°~120°, the groove depth is 80μm~200μm, and the groove spacing between adjacent V-grooves is 0.1mm~1mm.

[0008] Optionally, in S1, the polydimethylsiloxane material forming the elastic working template is formed by mixing polydimethylsiloxane prepolymer and curing agent in a mass ratio of 8 to 10:1, and then curing at room temperature for more than 8 hours.

[0009] Optionally, in S2, the glass substrate is ultrasonically cleaned with the alkaline cleaning solution for 4 to 8 minutes, and then ultrasonically cleaned with pure water or ultrapure water for 10 to 20 minutes. After ultrasonic cleaning, the glass substrate is slowly lifted out of the pure water and dried.

[0010] Optionally, in S2, the nanoimprint adhesive is a low-stress UV-curable nanoimprint adhesive, and the curing shrinkage rate of the nanoimprint adhesive is less than 3%; the nanoimprint adhesive is applied by spin coating, and the thickness of the imprint adhesive layer formed is 80μm~200μm, and the thickness of the imprint adhesive layer is not less than the groove depth of the mother V groove array, and the thickness uniformity error is not greater than 5μm.

[0011] Optionally, in S3, the planar loading force is greater than 0 and not greater than 50N, and the pressure holding time is 40s~80s.

[0012] Optionally, in S4, the overall ultraviolet irradiation uses ultraviolet light with a wavelength of 365nm, the ultraviolet irradiation time is 60s, and the planar loading force is maintained during the ultraviolet irradiation process.

[0013] Optionally, in S5, after the planar loading force is released or reduced, the mold is peeled off starting from one side of the elastic working template and gradually peeled off towards the opposite side.

[0014] Optionally, in S6, the temperature of the constant temperature heat treatment is 115℃~125℃, and the time of the constant temperature heat treatment is 40min~80min.

[0015] Optionally, in S6, during the constant temperature heat treatment, the side of the glass substrate away from the resin structure layer is attached to the planar support member, and the glass substrate is pressed by a limiting member disposed around the periphery of the glass substrate, the limiting member being spaced apart from the resin structure layer; after the constant temperature heat treatment is completed, the glass substrate is cooled to room temperature while maintaining the pressed state, and then the pressing of the glass substrate is released.

[0016] The beneficial effects that this application can achieve are: This application utilizes a master mold to create an elastic working template with a V-shaped convex ridge array. Under planar loading, the V-shaped convex ridge array is pressed into the imprinted adhesive layer on the surface of the glass substrate, thereby replicating and forming a V-groove array within the resin structural layer. This eliminates the need for V-groove cutting on the final glass substrate, reducing the risk of glass cutting damage. Maintaining the V-groove contour through pressurized bonding and one-time overall UV curing helps preserve the V-groove profile. Gradual demolding starting from one side of the template reduces instantaneous separation load. Post-demolding isothermal heat treatment improves the hardness or dimensional stability of the resin V-groove structure, thereby enhancing replication integrity and batch consistency. Attached Figure Description

[0017] Figure 1 This is a schematic cross-sectional view of the glass-based resin V-groove structure obtained by the nanoimprinting preparation method in Example 1 of this application. Figure 2 This is a schematic cross-sectional view of the female mold used in Embodiment 1 of this application; Figure 3 This is a cross-sectional schematic diagram of the flexible working template used in Embodiment 1 of this application; Among them, 1-glass substrate, 2-resin V-groove structure layer. Detailed Implementation

[0018] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0019] It should be noted that, in this application, "V-groove angle" refers to the angle formed between the two sidewalls of the V-groove on a cross section perpendicular to the extension direction of the V-groove; "groove depth" refers to the vertical distance from the reference plane on the upper surface of the resin structural layer to the lowest point of the V-groove; and "groove spacing" refers to the distance between the center lines of two adjacent V-grooves.

[0020] The term "groove depth relative replication error" as used in this application refers to the percentage of the absolute value of the difference between the finished V-groove depth and the corresponding mother V-groove depth to the mother V-groove depth. It is used to characterize the groove depth replication state of the V-groove structure after template making, imprinting, curing, demolding and constant temperature heat treatment.

[0021] Reference Figures 1-3 The first embodiment of this application provides a method for preparing a glass-based resin V-groove structure using nanoimprinting, comprising the following steps: S1. Glass is selected as the substrate for the master mold. A V-groove array is formed on one side of the master mold substrate by a combination of precision cutting and etching. The included angle of the V-grooves in the array is 75°, the groove depth is 140μm, and the groove spacing between adjacent V-grooves is 0.55mm.

[0022] The external dimensions of the master mold substrate are determined based on the dimensions of the glass-based resin V-groove structure to be prepared, and there are no special limitations on its external dimensions. The master mold is only used as a replica mold for the subsequent elastic working template and is not directly used as the final optical device. Therefore, the structural accuracy of the master V-groove array is the main control target during the preparation of the master mold. Minor machining marks or scratches that do not affect the contour accuracy of the master V-groove array are allowed to exist, and the same master mold can be reused for the reproduction of the elastic working template.

[0023] Polydimethylsiloxane prepolymer and curing agent were mixed at a mass ratio of 9:1. After thorough mixing, the mixture was applied to the side containing the master V-groove array and cured at room temperature for 10 hours. After curing, the polydimethylsiloxane material was separated from the master mold to obtain a polydimethylsiloxane elastic working template. Since the elastic working template was formed by replicating the master V-groove array, the molding surface of the elastic working template formed a V-shaped convex ridge array complementary to the master V-groove array.

[0024] In actual mass production, the same flexible working template can be repeatedly imprinted multiple times, completing more than 20 imprinting operations while maintaining the integrity of the molding surface. The pattern replication accuracy of the flexible working template can reach the 5nm level, and the structural differences between different batches of flexible working templates can be reduced through high-precision master molds and flexible mold flipping methods.

[0025] S2. Optical glass is selected as the glass substrate. First, the glass substrate is placed in an alkaline cleaning solution for ultrasonic cleaning for 6 minutes. The alkaline cleaning solution combined with ultrasonic action removes oil, dust and particulate matter from the surface of the glass substrate. Then, the glass substrate is placed in pure water for ultrasonic cleaning for another 15 minutes to remove residual alkaline cleaning solution and impurities from the surface of the glass substrate.

[0026] After ultrasonic cleaning with pure water, the glass substrate is slowly lifted out of the pure water and dried using the drying function of the cleaning equipment. In this embodiment, the glass substrate is not subjected to plasma surface activation after the above cleaning and drying; it is directly coated with nanoimprint adhesive. Alkaline ultrasonic cleaning combined with slow-pull drying with pure water simplifies the surface treatment process of the glass substrate.

[0027] A low-stress UV-curable nanoimprinting adhesive was selected as the nanoimprinting adhesive. In this embodiment, a nanoimprinting adhesive with a curing shrinkage rate of less than 1% is preferably used, thus simultaneously meeting the requirement of a curing shrinkage rate of less than 3%. The viscosity of the nanoimprinting adhesive before curing is 300 mPa·s.

[0028] The nanoimprint embossing adhesive is spin-coated onto one side surface of a glass substrate to form an embossing adhesive layer with a thickness of 150 μm. The thickness of the embossing adhesive layer is not less than the groove depth of the mother V-groove array, and the thickness uniformity error of the embossing adhesive layer is controlled to be no greater than 5 μm. Furthermore, the overall thickness uniformity error of the embossing adhesive layer is preferably no greater than 2%. By controlling the curing shrinkage rate of the nanoimprint embossing adhesive and the thickness uniformity of the embossing adhesive layer, it is beneficial to reduce the dimensional variation differences at different locations in the imprinted area during the subsequent curing process.

[0029] An unformed area is provided around the periphery of the glass substrate, so that the unformed area is separated from the formed area forming the V-groove array. The unformed area can be used to hold the glass substrate during subsequent heat treatment.

[0030] S3. Position the V-shaped convex ridge array of the elastic working template toward the imprinting adhesive layer, load the glass substrate and the elastic working template into the SUSS flat-panel nanoimprinting device, and position the V-shaped convex ridge array opposite the imprinting adhesive layer.

[0031] A planar loading force of 25N is applied to the elastic working template and the glass substrate using the flat nanoimprinting device, and the pressure is maintained for 60s. The loading force applied by the device acts on the elastic working template through the relatively set imprinting plane, so that the entire forming area of ​​the elastic working template is subjected to surface pressure, thereby pressing each V-shaped protrusion into the imprinting adhesive layer.

[0032] During loading, the nano-imprint adhesive flows under pressure and gradually fills the molding space between the V-shaped ridges and between the elastic working template and the glass substrate, until the molding surface of the elastic working template and the imprint adhesive layer form a stable bond. This embodiment uses a flat-plate imprinting method to complete the imprinting process. Compared with the area-by-area rolling method, it can apply surface pressure to the entire molding area during the same imprinting process. The SUSS flat-plate nano-imprinting equipment is used for uniform planar pressure, ensuring that the V-shaped ridge array is fully pressed into the imprint adhesive layer and that the imprint adhesive layer is fully bonded to the molding surface of the elastic working template.

[0033] S4. Maintain the pressure bonding state between the elastic working template formed in S3 and the glass substrate, that is, under the condition of maintaining a 25N planar loading force, perform ultraviolet curing on the imprinted adhesive layer.

[0034] This embodiment uses ultraviolet light with a wavelength of 365nm and an irradiation time of 60s. The ultraviolet irradiation covers the entire imprinting area, allowing the imprinting adhesive layer to be cured in one go while the elastic working template is kept pressed, forming a resin structure layer bonded to the glass substrate.

[0035] During UV curing, the pressure of the elastic working template on the imprinted adhesive layer is not released beforehand, allowing the imprinted adhesive to complete cross-linking and curing within the shape defined by the V-shaped ridges. This ensures that the formed resin structure layer maintains the contour replicated by the V-shaped ridges. This embodiment employs full-area UV irradiation, enabling simultaneous UV curing of the imprinted adhesive across the entire molding area. Full-area UV curing is performed under pressure bonding, ensuring synchronous cross-linking of the imprinted adhesive.

[0036] S5. After UV curing is completed, slowly release the planar loading force. While avoiding sudden separation of the elastic working template from the resin structural layer, manually start to peel off the template from one side.

[0037] During the demolding process, the elastic working template is gradually lifted, allowing the separation interface between the elastic working template and the resin structural layer to gradually advance from the starting side to the opposite side until the elastic working template is completely separated from the resin structural layer. This embodiment does not limit the specific left or right direction of manual demolding; it only requires that the demolding process start from one side and gradually advance to the other side.

[0038] By employing the aforementioned gradual demolding method, different areas of the elastic working template separate sequentially from the resin structural layer. This avoids a large instantaneous separation load caused when the entire elastic working template detaches from the resin structural layer simultaneously, thereby reducing the shearing and peeling effects on the resin V-groove structure during demolding. After the elastic working template has completely detached, the side of the resin structural layer facing away from the glass substrate forms and exposes the V-groove array. Slow unloading and gradual demolding are used to reduce shear stress and protect the V-groove microstructure.

[0039] S6. The demolded glass substrate and the resin structure layer formed on one side of the glass substrate are subjected to constant temperature heat treatment.

[0040] Specifically, the side of the glass substrate facing away from the resin structural layer is attached to a flat, heat-resistant planar support, providing planar support for the glass substrate. Multiple limiting members are spaced apart around the periphery of the glass substrate, with each limiting member's pressing portion acting on a non-molded area around the periphery, thereby pressing the glass substrate onto the planar support. Each limiting member avoids the resin structural layer, ensuring that it does not contact the resin V-groove structure during the entire heat treatment process.

[0041] The glass substrate, resin structural layer, and planar support, all in the aforementioned pressed state, were placed together in a constant-temperature heating device and heat-treated at 120°C for 60 minutes. This constant-temperature heat treatment further promoted the cross-linking of the UV-cured nanoimprint adhesive and improved the hardness and dimensional stability of the resin V-groove structure.

[0042] After the isothermal heat treatment is completed, the limiting member is not immediately released from holding the glass substrate. Instead, the glass substrate is cooled while still in contact with the planar support and with its periphery held in place. Once the glass substrate and resin structural layer have cooled to room temperature, the limiting member is released and the glass substrate is removed from the planar support to reduce warping deformation of the glass substrate and its surface resin structural layer during the heat treatment and cooling process.

[0043] In this embodiment, the isothermal heat treatment serves as a heat reinforcement step after UV curing, eliminating the need for a separate secondary UV curing. The preferred heat curing time is 1 hour, which further enhances the crosslinking degree of the imprinting adhesive and the hardness of the groove structure.

[0044] Therefore, we obtain Figure 1 The glass-based resin V-groove structure shown has a glass substrate forming a glass substrate 1 and a resin structure layer cured on one side of the glass substrate forming a resin V-groove structure layer 2.

[0045] In this embodiment, a high-precision master mold is used to create an elastic working template, which is then used to replicate the V-groove array in the nano-imprinting adhesive on the surface of the glass substrate. Ultimately, the glass substrate body does not need to be directly cut into V-grooves. At the same time, the combination of low-shrinkage imprinting adhesive, planar imprinting, overall UV curing under pressure, progressive demolding, and constant-temperature thermal reinforcement processes helps to improve the replication integrity and dimensional stability of the resin V-groove structure.

[0046] As an optional implementation, the second embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: in S1, the master mold substrate is glass, and the master V-groove array is formed by a combination of precision cutting and etching; the included angle of the V-grooves of the master V-groove array is 30°, the groove depth is 80μm, and the groove spacing between adjacent V-grooves is 0.1mm.

[0047] As an optional implementation, the third embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: In S1, the master mold substrate is silicon, and the master V-groove array is formed by a combination of precision cutting and etching; the included angle of the V-grooves of the master V-groove array is 120°, the groove depth is 170μm, and the groove spacing between adjacent V-grooves is 1mm; In S2, the thickness of the formed imprint adhesive layer is 200μm.

[0048] As an optional implementation, the fourth embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: In S1, the polydimethylsiloxane material forming the elastic working template is formed by mixing polydimethylsiloxane prepolymer and curing agent in a mass ratio of 8:1 and curing at room temperature for 8 hours.

[0049] As an optional implementation, the fifth embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: In S1, the polydimethylsiloxane material forming the elastic working template is formed by mixing polydimethylsiloxane prepolymer and curing agent in a mass ratio of 10:1 and curing at room temperature for 15 hours.

[0050] As an optional implementation, the sixth embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: in S2, the glass substrate is ultrasonically cleaned with the alkaline cleaning solution for 4 minutes, and then ultrasonically cleaned with ultrapure water for 10 minutes; after the ultrasonic cleaning with ultrapure water is completed, the glass substrate is slowly lifted out of the pure water and dried.

[0051] As an optional implementation, the seventh embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: in S2, the glass substrate is ultrasonically cleaned with the alkaline cleaning solution for 8 minutes, and then ultrasonically cleaned with pure water for 20 minutes; after the pure water ultrasonic cleaning is completed, the glass substrate is slowly lifted out of the pure water and dried.

[0052] As an optional implementation, the eighth embodiment of this application provides a method for preparing a glass-based resin V-groove structure using nanoimprinting. The difference from the first embodiment is that, in S1, the groove depth of the mother V-groove array is 80 μm; in S2, the nanoimprinting adhesive is a low-stress UV-curable nanoimprinting adhesive with a curing shrinkage rate of 1%, and the nanoimprinting adhesive is applied by spin coating, forming an imprinting adhesive layer with a thickness of 90 μm and a thickness uniformity error of no more than 1 μm. The remaining steps and process parameters are the same as in the first embodiment.

[0053] As an optional implementation, the ninth embodiment of this application provides a method for preparing a glass-based resin V-groove structure using nanoimprinting. The difference from the first embodiment is that, in S1, the groove depth of the mother V-groove array is 190 μm; in S2, the nanoimprinting adhesive is a low-stress UV-curable nanoimprinting adhesive with a curing shrinkage rate of 2.9%, and the nanoimprinting adhesive is applied by spin coating, forming an imprinting adhesive layer with a thickness of 200 μm and a thickness uniformity error of no more than 5 μm. The remaining steps and process parameters are the same as in the first embodiment.

[0054] As an optional implementation, the tenth embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: in S3, the planar loading force is 5N and the holding time is 40s.

[0055] As an optional implementation, the eleventh embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: in S3, the planar loading force is 50N and the holding time is 80s.

[0056] As an optional implementation, the twelfth embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: in S6, the temperature of the isothermal heat treatment is 115°C and the time of the isothermal heat treatment is 40 min.

[0057] As an optional implementation, the thirteenth embodiment of this application provides a method for preparing a glass-based resin V-groove structure by nanoimprinting. The difference from the first embodiment is that some process parameters are different: in S6, the temperature of the isothermal heat treatment is 125°C and the time of the isothermal heat treatment is 80 min.

[0058] The above are merely preferred embodiments of this application and do not limit the patent scope of this application. Any equivalent structural or procedural transformations made using the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of this application.

[0059] This application also provides a first comparative example, which differs from the first embodiment in that step S6 is different, while the remaining steps and process parameters are the same as those in the first embodiment. In step S6, after the elastic working template detaches from the resin structure layer, the glass substrate and the resin structure layer are no longer subjected to constant temperature heat treatment. Instead, the resulting glass-based resin V-groove structure is directly placed in a room temperature environment, so that the resin structure layer formed by UV curing maintains its original cured state.

[0060] This comparative example is mainly used to compare with the first embodiment the effect of constant temperature heat treatment after demolding on the subsequent crosslinking degree, surface hardness and V-groove size stability of the resin structural layer.

[0061] This application also provides a second comparative example, which differs from the first embodiment in that S5 is different, while the remaining steps and process parameters are the same as those in the first embodiment.

[0062] In S5, after UV curing is completed and the planar loading force is released, instead of a gradual demolding method that pushes the separation interface from one side of the elastic working template to the opposite side, the periphery of the elastic working template is lifted at the same time, so that the elastic working template is completely separated from the resin structure layer.

[0063] This comparative example is mainly used to compare the effects of progressive demolding and overall demolding on the integrity of the V-groove wall, groove opening and groove bottom with the first embodiment.

[0064] This application also provides a third comparative example, which differs from the first embodiment in that S3 is different, while the remaining steps and process parameters are the same as those in the first embodiment.

[0065] In S3, instead of using a flat nanoimprinting device to apply planar loading force to the entire forming area of ​​the elastic working template, a flexible pressure roller is used to gradually roll from one side of the elastic working template to the opposite side. The total normal load during the rolling process is 25N, and the rolling time is 60s, so that the elastic working template and the imprinting adhesive layer are bonded to each area.

[0066] This comparative example is mainly used to compare with the first embodiment the effects of planar pressure on the entire molding area and rolling on each area on the filling state of the imprinting adhesive, the replica size of the V-groove, and the molding consistency at different positions.

[0067] To verify the influence of different process parameters and process steps on the molding quality of glass-based resin V-groove structures, the performance of glass-based resin V-groove structures prepared in Examples 1-13 and Comparative Examples 1-3 was tested.

[0068] The mother V-groove array and the resulting glass-based resin V-groove structure were inspected using a high-magnification microscope and a three-dimensional measuring instrument. During inspection, corresponding inspection positions were selected in both the mother and resulting V-groove arrays. The V-groove depth, groove spacing, and V-groove angle at each corresponding position were measured using the three-dimensional measuring instrument. The groove depth of the finished V-groove was compared with the groove depth of the corresponding position in the mother V-groove to determine the relative replication error of the groove depth. The relative replication error of the groove depth referred to in this application is the percentage of the absolute value of the difference between the groove depth of the finished V-groove and the corresponding groove depth of the mother V-groove to the total groove depth of the mother V-groove.

[0069] The relative replication error of the trench depth obtained at different detection positions in the same test group was statistically analyzed, and its average value was taken as the relative replication error of the trench depth in the test group.

[0070] The morphology of the groove opening, walls, and bottom of the obtained V-groove array was observed using a high-powered microscope to determine whether the V-groove outline was complete and whether there were any incompletely formed areas, localized missing resin, air bubbles, or unfilled sharp corners. The cavity filling rate was determined based on the proportion of the area with a complete V-groove outline to the target V-groove forming area. A higher cavity filling rate indicates that the nano-imprint adhesive has fully filled the corresponding forming area of ​​the elastic working template. Simultaneously, the V-groove array after demolding was observed using a high-powered microscope. V-grooves with groove opening chipping, groove wall tearing, localized resin shedding, or significant V-groove structural deformation were identified as demolding defective V-grooves. The demolding defect rate was determined based on the proportion of demolding defective V-grooves in the detected area to the total number of V-grooves detected. A lower demolding defect rate indicates that the V-groove structure formed during the demolding process remained more complete.

[0071] The surface hardness of the resin structural layer was detected using a nanoindenter. The test was performed at multiple representative locations in the V-groove structural layer and the average value was taken to characterize the degree of curing and reinforcement of the resin structural layer after UV curing and subsequent isothermal heat treatment.

[0072] After each embodiment and comparative example underwent the corresponding processing and was restored to room temperature, a three-dimensional measuring instrument was used to detect the surface height change of the glass substrate. Using a reference plane of the glass substrate as a reference, the maximum height deviation of different positions on the glass substrate relative to the reference plane was determined, and this maximum height deviation was taken as the maximum warpage of the glass substrate. A smaller maximum warpage indicates better overall dimensional stability of the glass substrate and resin structural layer during curing, heat treatment, and cooling.

[0073]

[0074] The test results from Examples 1 to 9 show that the dimensions of the mother V-groove structure, the preparation conditions of the polydimethylsiloxane elastic working template, the cleaning conditions of the glass substrate, and the parameters of the nanoimprint adhesive layer all affect the replication effect of the glass-based resin V-groove structure. Example 1 achieved a cavity filling rate of 99.31%, a relative replication error of 0.58% in groove depth, and a demolding defect rate of 0.32%, demonstrating good overall performance in these aspects. Example 2, by using a smaller V-groove angle, groove depth, and groove spacing, saw a decrease in the cavity filling rate to 98.08%, an increase in the relative replication error of groove depth to 1.12%, and an increase in the demolding defect rate to 0.92%, indicating that a smaller groove spacing and a sharper V-groove structure increase the difficulty of localized colloid molding and subsequent template detachment. Example 3 uses a larger V-groove angle, groove depth, and groove spacing, while changing the master mold conditions. Its cavity filling rate is 98.62%, and the relative replication error of the groove depth is 0.96%. This indicates that changes in the V-groove structure dimensions and master mold conditions lead to changes in the final replication state. The larger groove depth requires the V-shaped convex ridge array to be further pressed into the imprinting adhesive layer, increasing the flow and redistribution distance of the imprinting adhesive during the molding process. The results of Examples 1, 2, and 3 show that different V-groove structure dimensions and their corresponding master mold and imprinting adhesive layer conditions all affect the final replication state of the V-groove structure. Under the condition of ensuring sufficient molding of the imprinting adhesive while also considering subsequent demolding, the process conditions used in Example 1 demonstrate a better overall replication effect.

[0075] Examples 4, 1, and 5 used polydimethylsiloxane prepolymer to curing agent mass ratios of 8:1, 9:1, and 10:1, respectively, and employed corresponding curing conditions. The cavity filling rates were 98.71%, 99.31%, and 98.95%, respectively; the relative replication errors of the groove depth were 0.83%, 0.58%, and 0.72%, respectively; and the demolding defect rates were 0.64%, 0.32%, and 0.51%, respectively. These results indicate that the polydimethylsiloxane material ratio and its degree of curing jointly affect the structural retention and flexibility of the elastic working template. When the rigidity of the elastic working template is relatively high, its adaptability to the local morphology of the glass substrate and the imprinting adhesive layer will be affected to some extent; when the flexibility of the elastic working template is relatively high, the elastic deformation generated during imprinting loading and template separation may also increase accordingly. Therefore, the elastic working template needs to balance the structural retention capability of the V-shaped rib array with its adhesion to the imprinting adhesive layer. Under the process conditions of this embodiment, the polydimethylsiloxane material preparation conditions used in Example 1 achieved good cavity filling, size replication, and demolding integrity.

[0076] The test results of Examples 6, 1, and 7 show that the cleaning conditions of the glass substrate also affect the subsequent imprinting state. In Example 6, when alkaline ultrasonic cleaning for 4 minutes and pure water ultrasonic cleaning for 10 minutes were used, the cavity filling rate was 98.43%, the relative replication error of the groove depth was 0.87%, and the demolding defect rate was 0.73%. After increasing the cleaning time to 6 minutes and 15 minutes as in Example 1, the above indicators improved to 99.31%, 0.58%, and 0.32%, respectively. In Example 7, after further increasing the alkaline ultrasonic cleaning time to 8 minutes and the pure water ultrasonic cleaning time to 20 minutes, the cavity filling rate was 99.08%, the relative replication error of the groove depth was 0.64%, and the demolding defect rate was 0.43%, which did not show a significant improvement compared to Example 1. Therefore, appropriately increasing the time for alkaline ultrasonic cleaning and pure water ultrasonic cleaning helps reduce residual oil, dust, and particulate matter on the glass substrate surface, improves the spreading state of the nanoimprint adhesive on the glass substrate surface, and enhances the adhesion between the elastic working template and the imprint adhesive layer. Once the cleaning time reaches a level sufficient to achieve a relatively clean glass substrate, further extending the cleaning time yields limited improvement. Therefore, the cleaning conditions used in Example 1 balance both the cleaning effect and processing efficiency of the glass substrate.

[0077] The test results of Examples 8, 1 and 9 show that, under the condition that the thickness of the imprinting adhesive layer matches the corresponding depth of the mother V groove, the depth of the V groove, the thickness of the imprinting adhesive layer and the curing shrinkage properties of the nano-imprinting adhesive will jointly affect the molding quality of the final V groove structure. Example 8 uses a mother V-groove depth of 80 μm and an imprinting adhesive layer of 90 μm, achieving a cavity filling rate of 97.66%, a relative replication error of 1.48% for groove depth, and a demolding defect rate of 0.86%. Example 1 uses a mother V-groove depth of 140 μm and an imprinting adhesive layer of 150 μm, increasing the cavity filling rate to 99.31%, reducing the relative replication error of groove depth to 0.58%, and decreasing the demolding defect rate to 0.32%. Example 9 uses a mother V-groove depth of 190 μm and an imprinting adhesive layer of 200 μm, while increasing the curing shrinkage rate of the nano-imprinting adhesive to 2.9%, still achieving a cavity filling rate of 99.17%, but increasing the relative replication error of groove depth to 1.36% and the maximum warpage to 10.9 μm.

[0078] Therefore, it can be seen that, under the condition that the thickness of the imprinting adhesive layer is greater than the corresponding depth of the mother V-groove and can meet the requirements of V-groove molding, the depth of the V-groove, the thickness of the imprinting adhesive layer, and the curing shrinkage performance of the nano-imprinting adhesive need to be matched with each other. In Example 8, when a smaller V-groove depth and a thinner imprinting adhesive layer are used, although the indentation depth of the V-shaped protrusion is smaller, the amount of adhesive available for the imprinting adhesive to flow and redistribute during the pressing process is relatively small, and its V-groove molding integrity and groove depth replication accuracy are lower than those of Example 1. In Example 9, a larger V-groove depth and a thicker imprinting adhesive layer are used, and the curing shrinkage rate of the nano-imprinting adhesive is higher. Although a high cavity filling rate can be maintained, the dimensional changes and residual stress generated during the curing process are correspondingly increased, thereby increasing the relative replication error of the groove depth and the warping of the glass substrate. Example 1, using a medium V-groove depth, a matching imprinting adhesive layer thickness, and a nano-imprinting adhesive with a low curing shrinkage rate, shows a better overall balance between cavity filling rate, groove depth replication accuracy, demolding integrity, and glass substrate dimensional stability.

[0079] The test results from Examples 10, 1, 11, and the third control example show that the planar loading force, holding time, and loading method directly affect the molding quality of the V-groove structure. In Example 10, when a relatively low planar loading force of 5N was applied and the pressure was held for 40s, the cavity filling rate was 95.46%, the relative replication error of the groove depth reached 2.38%, and the demolding defect rate was 1.64%. This indicates that when the loading is insufficient, the V-shaped convex ridge array cannot be fully pressed into the imprinted adhesive layer, and it is difficult to form a stable and sufficient adhesion between the molding surface of the elastic working template and the imprinted adhesive layer, thus affecting the full molding of the V-groove structure. In Example 1, after applying a planar loading force of 25N and holding the pressure for 60s, the cavity filling rate increased to 99.31%, the relative replication error of the groove depth decreased to 0.58%, and the demolding defect rate decreased to 0.32%. This indicates that appropriately increasing the planar loading force and extending the holding time can promote the flow of nano-imprinting adhesive under pressure, allowing the V-shaped convex ridge array to be further pressed into the imprinting adhesive layer, and improving the degree of adhesion between the forming surface of the elastic working template and the imprinting adhesive layer.

[0080] In Example 11, the planar loading force was further increased to 50 N and the holding time was extended to 80 s. The cavity filling rate reached 99.52%, which was higher than that of Example 1, indicating that increasing the planar loading force could further promote the full molding of the V-groove structure. However, the relative replication error of the groove depth in Example 11 increased to 0.76%, the demolding defect rate increased to 0.66%, and the maximum warpage increased to 9.5 μm, all of which were inferior to the corresponding indicators of Example 1. This shows that a larger planar loading force and holding time are not necessarily better. Excessive loading can increase the compression deformation of the polydimethylsiloxane elastic working template and may also leave a large residual stress in the cured resin structure layer, thus adversely affecting the V-groove size replication, demolding integrity, and subsequent dimensional stability. In Example 1, using a planar loading force of 25 N and a holding time of 60 s, although the cavity filling rate was slightly lower than that of Example 11, the relative replication error of the groove depth, the demolding defect rate, and the maximum warpage were all lower. Therefore, a better overall effect could be achieved between full molding and dimensional stability.

[0081] The third comparative example uses a flexible pressure roller to gradually roll the elastic working template from one side to the opposite side. Under the conditions of a total normal load of 25N and a rolling time of 60s, its cavity filling rate is 96.84%, the relative replication error of the groove depth is 1.72%, and the demolding defect rate is 1.18%. Compared with Example 1, which has a similar loading amount and action time, the molding performance of the third comparative example is significantly reduced. The reason is that during the area-by-area rolling process, different positions of the elastic working template are subjected to loading in sequence. Local deformation of the template and migration of the adhesive can easily occur between the already compressed area, the currently compressed area, and the uncompressed area, making it difficult to maintain a relatively consistent pressing state at different positions simultaneously. In contrast, the flat-plate nanoimprinting equipment can subject the entire molding area of ​​the elastic working template to planar loading during the same imprinting process, so that the V-shaped convex ridge array at each position is pressed into the imprinting adhesive layer more synchronously, which is beneficial to improving the molding consistency of different areas. Therefore, the beneficial effect of the flat-plate nanoimprinting method is not only due to the magnitude of the loading force, but also related to its ability to form a relatively stable surface pressure state throughout the molding area.

[0082] The test results from Example 1 and the second control example show that progressive demolding mainly affects the structural integrity of the V-groove structure during the template separation process after UV curing. Example 1 and the second control example used the same master mold, elastic working template, glass substrate pretreatment, imprinting adhesive layer, planar imprinting, and UV curing conditions in S1 to S4. Their cavity filling rates were 99.31% and 99.30%, respectively, and the surface hardness of the resin structural layer was 0.392 GPa and 0.391 GPa, respectively. These two indicators are basically consistent, indicating that changing the demolding method does not significantly affect the imprinted state and resin curing degree formed before demolding. Example 1 used a progressive demolding method starting from one side of the elastic working template and gradually advancing the separation interface between the elastic working template and the resin structural layer towards the opposite side, resulting in a demolding defect rate of only 0.32%. In the second control example, after the elastic working template was completely detached from the resin structural layer, the demolding defect rate increased to 3.62%, and the relative replication error of the groove depth increased from 0.58% to 0.66%.

[0083] The above results indicate that when the elastic working template detaches from the resin structural layer simultaneously, a large area of ​​the elastic working template and the cured resin structural layer undergo interfacial separation at approximately the same time. The separation load acts simultaneously on the openings and walls of multiple V-grooves, easily leading to localized stress concentrations at the V-groove corners, openings, and sidewalls. This increases the likelihood of opening defects, wall tears, and the removal of localized resin structures by the template. By employing a progressive demolding method, the actual separation area between the elastic working template and the resin structural layer gradually moves towards the opposite side along the separation interface, transforming the original large-area simultaneous separation into continuous separation in localized areas. This allows the demolding load to be gradually released along the separation interface, thereby reducing the instantaneous peel load and shear force on the V-groove structure. The second control example shows little difference from Example 1 in terms of cavity filling rate and resin structural layer surface hardness, but a significant difference in demolding defect rate. This further demonstrates that the main function of progressive demolding is to protect the already cured V-groove structure, rather than altering the preceding imprinting or curing process. Therefore, this application adopts a demolding method that starts from one side of the elastic working template and gradually advances the separation interface to the opposite side, which helps to reduce the damage to the V-groove structure during demolding and improve the structural integrity of the finished V-groove array.

[0084] The test results from Examples 12, 1, 13, and the first control example show that the isothermal heat treatment conditions after demolding affect the subsequent curing state and dimensional stability of the resin structural layer. In the first control example, omitting the isothermal heat treatment, the surface hardness of the resin structural layer was 0.318 GPa, the relative replication error of the groove depth was 1.26%, and the maximum warpage was 12.7 μm. In Example 12, after isothermal heat treatment at 115℃ for 40 min, the surface hardness of the resin structural layer increased to 0.351 GPa, the relative replication error of the groove depth decreased to 0.63%, and the maximum warpage decreased to 8.2 μm. In Example 1, after isothermal heat treatment at 120℃ for 60 min, the surface hardness of the resin structural layer further increased to 0.392 GPa, the relative replication error of the groove depth decreased to 0.58%, and the maximum warpage decreased to 7.4 μm. The above results indicate that constant-temperature heat treatment of the glass substrate and resin structural layer after UV curing and demolding is beneficial to further improve the curing degree and hardness of the resin structural layer and improve the dimensional retention of the resin V-groove structure.

[0085] In Example 13, by increasing the isothermal heat treatment temperature to 125°C and extending the heat treatment time to 80 minutes, the surface hardness of the resin structural layer further increased to 0.421 GPa, the highest value among Examples 12, 1, and 13. This indicates that increasing the isothermal heat treatment temperature and extending the treatment time can further promote the formation of a more stable cured state of the resin structural layer. However, the relative replication error of the groove depth in Example 13 also increased to 0.81%, and the maximum warpage increased to 9.6 μm, both higher than in Example 1. This shows that a higher degree of isothermal heat treatment is not necessarily more beneficial. As the heat treatment temperature increases and the treatment time extends, the further shrinkage of the resin structural layer and the influence of the thermal deformation difference between the resin material and the glass substrate also increase, which may adversely affect the maintenance of the V-groove dimensions and the flatness of the glass substrate. The heat treatment temperature and time used in Example 12 were relatively low, and the surface hardness of its resin structure layer was also relatively low. Although Example 13 could obtain a higher hardness of the resin structure layer, the size replication error and glass substrate warping were relatively increased. After using constant temperature heat treatment conditions of 120°C for 60 minutes in Example 1, a better overall balance was achieved between the hardness of the resin structure layer, the size replication accuracy of the V groove, and the flatness of the glass substrate.

[0086] Meanwhile, in Example 1, during the isothermal heat treatment, the side of the glass substrate facing away from the resin structural layer is bonded to the planar support, and the glass substrate is held in a pressed state by limiting members located around the periphery of the glass substrate. After the isothermal heat treatment is completed, the pressing is not immediately released, but the glass substrate is cooled to room temperature while still in contact with the planar support. This method can provide continuous planar constraint on the glass substrate during the subsequent curing of the resin structural layer and the co-cooling of the glass substrate and the resin structural layer, which helps maintain the planar state of the glass substrate and reduces the possibility of significant warping during heat treatment and cooling.

[0087] Based on the test results of various embodiments and comparative examples, it can be seen that this application replicates a polydimethylsiloxane elastic working template by using a mother V-groove array. A nanoimprint adhesive layer adapted to the V-groove forming depth is formed on the surface of a glass substrate that has been cleaned with alkaline ultrasonication. The V-shaped convex ridge array is pressed into the imprint adhesive layer using a flat nanoimprinting device. The imprint adhesive layer is then cured under ultraviolet light while keeping the elastic working template and the glass substrate in pressure. Subsequently, a progressive demolding and constant temperature heat treatment are performed. This method can replicate and form a V-groove array in the resin structure layer on the surface of the glass substrate without directly cutting the V-groove into the final glass substrate body.

[0088] The test results also show that the V-groove structure dimensions, elastic working template preparation conditions, glass substrate cleaning conditions, imprinting adhesive layer parameters, planar loading conditions, and isothermal heat treatment conditions all affect the replication state of the final resin V-groove structure. When the various process conditions are within a mutually compatible range, the degree of molding of the imprinting adhesive, the accuracy of V-groove size replication, the integrity of demolding, and the subsequent dimensional stability of the resin structure layer can be well balanced. Among them, flat nanoimprinting is conducive to forming a more stable pressing state in the entire molding area, improving the molding consistency of V-groove structures at different locations; maintaining the pressurized bonding state for overall UV curing is conducive to completing resin curing under the contour state defined by the V-shaped convex ridge array; progressive demolding can significantly reduce the possibility of V-groove structure defects during the separation of the elastic working template; and isothermal heat treatment after demolding is conducive to improving the hardness and dimensional stability of the resin structure layer. Therefore, this application can improve the replication integrity, dimensional stability, and batch molding consistency of glass-based resin V-groove structures while reducing the risk of direct cutting damage to the glass substrate.

Claims

1. A method for preparing a glass-based resin V-groove structure using nanoimprinting, characterized in that, Includes the following steps: S1. A mother V-groove array is formed on one side of the mother mold substrate, and a polydimethylsiloxane elastic working template is made based on the mother V-groove array. The forming surface of the elastic working template has a V-shaped convex ridge array that is complementary to the mother V-groove array. S2. The glass substrate is ultrasonically cleaned using an alkaline cleaning solution. After the cleaned glass substrate is dried, a nano-imprint adhesive is coated on one side of the glass substrate to form an imprint adhesive layer. S3. Orient the V-shaped convex ridge array toward the imprinting adhesive layer, and apply a planar loading force to the elastic working template and the glass substrate using a flat nanoimprinting device, so that the V-shaped convex ridge array is pressed into the imprinting adhesive layer, and the forming surface of the elastic working template is bonded to the imprinting adhesive layer. S4. While keeping the elastic working template and the glass substrate pressed together, the imprinting adhesive layer is subjected to overall ultraviolet irradiation to cure the nano-imprinting adhesive and form a resin structure layer. S5. After UV curing, the elastic working template is gradually peeled off from one side, so that the separation interface between the elastic working template and the resin structure layer is gradually advanced from one side to the opposite side, so that the V-groove array formed on the side of the resin structure layer away from the glass substrate is exposed. S6. The demolded glass substrate and the resin structural layer are subjected to constant temperature heat treatment to obtain a glass-based resin V-groove structure.

2. The method for preparing a glass-based resin V-groove structure by nanoimprinting as described in claim 1, characterized in that, In S1, the master mold substrate is glass or silicon, and the master V-groove array is formed by precision cutting, etching, or a combination of precision cutting and etching; the included angle of the V-groove array is 30°~120°, the groove depth is 80μm~200μm, and the groove spacing between adjacent V-grooves is 0.1mm~1mm.

3. The method for preparing a glass-based resin V-groove structure by nanoimprinting as described in claim 1 or 2, characterized in that, In S1, the polydimethylsiloxane material forming the elastic working template is formed by mixing polydimethylsiloxane prepolymer and curing agent in a mass ratio of 8 to 10:1, and then curing at room temperature for more than 8 hours.

4. The method for preparing a glass-based resin V-groove structure by nanoimprinting as described in claim 1, characterized in that, In step S2, the glass substrate is ultrasonically cleaned with the alkaline cleaning solution for 4 to 8 minutes, and then ultrasonically cleaned with pure water or ultrapure water for 10 to 20 minutes. After ultrasonic cleaning, the glass substrate is slowly lifted out of the pure water and dried.

5. The method for preparing a glass-based resin V-groove structure by nanoimprinting as described in claim 1, characterized in that, In S2, the nanoimprint adhesive is a low-stress UV-curable nanoimprint adhesive, and the curing shrinkage rate of the nanoimprint adhesive is less than 3%. The nanoimprint adhesive is applied by spin coating, and the thickness of the imprint adhesive layer formed is 80μm~200μm. The thickness of the imprint adhesive layer is not less than the groove depth of the mother V groove array, and the thickness uniformity error is not greater than 5μm.

6. The method for preparing a glass-based resin V-groove structure by nanoimprinting as described in claim 1, characterized in that, In S3, the planar loading force is greater than 0 and not greater than 50N, and the pressure holding time is 40s~80s.

7. The method for preparing a glass-based resin V-groove structure by nanoimprinting as described in claim 1, characterized in that, In S4, the overall ultraviolet irradiation uses ultraviolet light with a wavelength of 365nm, the ultraviolet irradiation time is 60s, and the planar loading force is maintained during the ultraviolet irradiation process.

8. The method for preparing a glass-based resin V-groove structure by nanoimprinting as described in claim 1, characterized in that, In S5, after the planar loading force is released or reduced, the mold is peeled off starting from one side of the elastic working template and gradually peeled off towards the opposite side.

9. The method for preparing a glass-based resin V-groove structure by nanoimprinting as described in claim 1, characterized in that, In S6, the temperature of the constant temperature heat treatment is 115℃~125℃, and the time of the constant temperature heat treatment is 40min~80min.

10. The method for preparing a glass-based resin V-groove structure by nanoimprinting as described in claim 1, characterized in that, In S6, during the constant temperature heat treatment, the side of the glass substrate away from the resin structure layer is attached to the planar support member, and the glass substrate is pressed by the limiting member provided on the periphery of the glass substrate. The limiting member is spaced apart from the resin structure layer. After the constant temperature heat treatment is completed, the glass substrate is cooled to room temperature while maintaining the pressed state, and then the pressing of the glass substrate is released.

Citation Information

Patent Citations

  • Method for manufacturing microlens array by soft mode impressing

    CN101339364B

  • Mold for a V-groove fiber array base block and fabrication method thereof

    US20040134786A1